2019
DOI: 10.3390/healthcare7040163
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Diagnosis Disclosure and Quality of Life in Elderly Cancer Patients

Abstract: Informed consent and patient autonomy rights require an optimal cancer diagnosis disclosure strategy to be used to update the patients and caregivers with the bad news. However, a cancer diagnosis disclosure may arouse anxiety and distress which increase patients’ and caregivers’ psychological burden. This study aims to explore the influence of cancer diagnosis disclosure on the quality of life in elderly cancer patients and their caregivers, and to introduce an effective way to disclose cancer diagnosis. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Rehabilitation based on the HBM can enhance the psychological resilience and rehabilitation compliance of patients, leading patients to actively participate in postoperative rehabilitation treatment and achieve a more ideal rehabilitation effect. Previous studies [ 26 , 27 ] have also shown that psychological interventions can improve survival in cancer patients. This evidence further proves the value of HBM psychological intervention in elderly gynaecological cancer patients in improving survival.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation based on the HBM can enhance the psychological resilience and rehabilitation compliance of patients, leading patients to actively participate in postoperative rehabilitation treatment and achieve a more ideal rehabilitation effect. Previous studies [ 26 , 27 ] have also shown that psychological interventions can improve survival in cancer patients. This evidence further proves the value of HBM psychological intervention in elderly gynaecological cancer patients in improving survival.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption that DR-TB causes in an individual’s ability to fulfil social and familial responsibilities were particularly worrisome and frightening for patients which needs timely intervention at the time of disclosing the diagnosis [ 5 , 22 ]. The disclosure process of DR-TB diagnosis could be made in a more sensitive and guided way as similar to other disease conditions, such as HIV and cancer, which could prepare the patients and caregivers mentally and socially [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study among elderly patients mentioned that not knowing their cancer condition results in an incomplete understanding of their diagnosis, which would hurt the trust relationship between these patients and physicians [ 21 ]. Based on a study of a total of 127 cancer patients and their caregivers, no significant difference was found before and after disclosing the cancer diagnosis to patients, while the quality of life could be improved with psychological care intervention [ 22 ]. We found that in patients with lung cancer, those who knew their cancer status had a better survival rate, while there are few studies about this issue in breast cancer patients [ 23 ].…”
Section: Introductionmentioning
confidence: 99%